ECO-SUFISM IN TAFSIR AL-AZHAR: HAMKA'S SUFISM INTERPRETATION'S CONTRIBUTION TO SUSTAINABLE ENVIRONMENTAL CONSERVATION IN INDONESIA - Kusnadi, Kusnadi; Zulfikar, Eko; Juwita, Rahma (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2023)
This article discusses the eco-sufism that Hamka built in his book Tafsir al-Azhar. This is motivated by the issue of environmental damage caused by, among other things, the anthropocentric paradigm, namely the notion that views humans as the center of the universe and has the right to exploit nature without considering its sustainability. Meanwhile, the hallmark of Hamka's interpretation of the verses of the Qur'an, which has a Sufi tendency, is trying to respond to environmental damage by offering sustainable environmental conservation efforts. Using a descriptive-explorative thematic method, Hamka built five efforts in preserving the environment with a Sufism approach, namely: paying attention to nature will strengthen faith in Allah; natural order is a form of God's existence; contemplation of nature will cause ‘isyq (longing) to God; managing nature as a provision to return to the presence of God; and being grateful for the results of natural resources by sharing them with others. In the interpretation of the verses about the five efforts, it appears that Hamka's interp retation tries to respond to environmental damage with a Sufi approach, which is seen as contributing to environmental conservation in a sustainable manner. Hamka provides a paradigm for balancing human rights and obligations to nature based on the holy book al-Qur'an so that it can be used as a guide for all Indonesians to realize a polite and moderate Islam towards nature by paying attention to environmental conservation.